2000
DOI: 10.1093/jn/130.5.1484s
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transport in the Brain: Routes of Zinc Influx and Efflux in Neurons

Abstract: Studies of the routes of entry and exit for zinc in different tissues and cell types have shown that zinc can use several pathways of exit or entry. In neurons, known pathways include (1) presynaptic release along with glutamate when synaptic vesicles empty their contents into the synaptic cleft, (2) voltage-gated L-type Ca(2+) channels and glutamate-gated channels that provide an entry route when cells are depolarized and that mediate extracellular zinc toxicity and (3) a plasma membrane transporter potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Bacterial and synaptic vesicle members of the zinctransporter family transport metal by a proton-coupledantiporter mechanism (Chao and Fu, 2004;Colvin et al, 2000a;Colvin et al, 2000b). In bacteria, the antiporter mechanism occurs with a stoichiometry of metal ion to proton close to 1:1 (Chao and Fu, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial and synaptic vesicle members of the zinctransporter family transport metal by a proton-coupledantiporter mechanism (Chao and Fu, 2004;Colvin et al, 2000a;Colvin et al, 2000b). In bacteria, the antiporter mechanism occurs with a stoichiometry of metal ion to proton close to 1:1 (Chao and Fu, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In bacteria, the antiporter mechanism occurs with a stoichiometry of metal ion to proton close to 1:1 (Chao and Fu, 2004). In synaptic vesicles, lumenal zinc accumulation is associated with vesicle alkalinization (Colvin et al, 2000a;Colvin et al, 2000b). Zinc accumulation probably increases the electrical gradient across the synaptic vesicle membrane while increasing the intravesicular pH, thus making the vesicle lumen more positive and favoring vesicular glutamate uptake (Reimer et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This ischemic neuronal death was prevented by the blockade of Zn 2+ translocation with Ca-EDTA, or the overexpression of metallothionein-1, a Zn 2+ -binding protein (van Lookeren et al, 1999). Zn 2+ ions enter into target cells through voltage-gated calcium channels (VGCC), NMDA, or AMPA/kainate glutamate receptors that are permeable to Ca 2+ , Na + /Ca 2+ exchanger, or Zn 2+ transporter (Freund and Reddig, 1994;Koh and Choi, 1994;Sensi et al, 1997;Sensi et al, 1999;Colvin et al, 2000). The entry and accumulation of Zn 2+ into neurons result in the transient generation of reactive oxygen species that mediate latent neuronal death .…”
Section: Production Of Reactive Oxygen Species By Transition Metalsmentioning
confidence: 99%
“…Passive influx through the neuronal membrane has been demonstrated to occur when extracellular levels of Zn 2ϩ are elevated, e.g. when Zn 2ϩ is added to the cell culture medium or when Zn 2ϩ is released from presynaptic vesicles (31). However, experiments using cultured neuronal cells have also demonstrated that Zn 2ϩ uptake can be stimulated upon activation of voltage-gated Ca 2ϩ or NMDA channels, for example (1)(2)(3)32).…”
Section: Zn 2ϩ Inhibits Adenylyl Cyclasementioning
confidence: 99%